E-Module Teaching Materials Based on Heyzine Flipbook on the Meaning of NKRI for Grade IV Elementary School - Puspitaningrum, Putri Norma; Witanto, Yuli (Journal of Education Reseach and Evaluation, 2024)
Currently, there are still many students who do not understand the Pancasila and Citizenship Education learning material. This is due to the lack of digital learning media to facilitate students' independent learning of PPKn. This research aims to develop a Civics e-module based on the Heyzine flipbook on the Meaning of the Unitary State of the Republic of Indonesia (NKRI) material for Class IV Elementary School. This type of research is R & D (Research and Development) development research. The development model in this research uses the ADDIE model. The research subjects were 1 media expert and 1 material expert. This small group trial was conducted on four students from class IV elementary school. The methods used to collect data are observation, interviews, questionnaires, and tests. The instruments used to collect data are validation sheets, questionnaire sheets, and test questions. The data analysis techniques used in this research are quantitative and qualitative data analysis. The research results, namely the assessment by material experts, obtained 87.50%, and media experts obtained a score of 84.09% with very good criteria. Evaluation of the effectiveness of use through the N-gain test obtained a score of 67.1% with moderate criteria, and the interpretation category was quite effective. Assessing responses via student questionnaires obtained an average score of 93% with very good criteria. It was concluded that e-modules are very suitable for use and can improve student learning outcomes in Pancasila and Citizenship Education subjects.